Practice research in free improvisation: Investigating relationships between interaction and musical identity - Prazeres Gonçalo (Jazz Research Journal, 2024)
This article focuses on interaction processes during the performance of free improvisation in the jazz idiom, and their correlation to the construction of individual musical identities. In this article, I regard musical identity as an artistic, dynamic and personal process characterized by continual communication, construction and negotiation with the surrounding social and cultural environment. Interaction, just like improvisation, is a fundamental defining element in jazz and free improvisation, playing a crucial role in shaping the musical identity of each musician during their performance. This is presented here as analogous to the moulding of individual identity in our everyday social interactions. This research is based on the author’s active participation in improvisation sessions and interviews with professional jazz musicians based in Lisbon, Portugal. Additionally, it explores how the context of free improvisation, when musical restrictions are minimized, intensifies the focus on the interactive improvisational process. This attribute makes free improvisation an ideal terrain for research on interaction and its relation with musical identity.